درجة الثقة التنظيمية لدى رؤساء الاقسام ومساعديهم بجامعة غرداية - بن حمدون, خديجة; بلعور, سليمان (جامعة الوادي - University of Eloued, 2020)
ملخص: تهدف هذه الدراسة إلى قياس درجة الثقة التنظيمية لدى رؤساء الأقسام ومساعديهم في جامعة غرداية، وذلك اتجاه كلا من الزملاء والمشرفين وادارة الجامعة، وقد استخدمنا في هذه الدراسة استبانة تم تصميمها وتوزيعها عل مجتمع الدراسة المتمثل في رؤساء الاقسام ومساعديهم في كليات الجامعة. وقد توصلت الدراسة إلى أنه توجد درجة عالية من الثقة التنظيمية لدى رؤساء الاقسام ومساعديهم في جامعة غرداية اتجاه مشرفيهم واتجاه زملائهم، في حين لا توجد درجة عالية من الثقة التنظيمية اتجاه الإدارة. وتوصي الدراسة بالمحافظة على الثقة الموجودة بين ورؤساء الأقسام ومساعديهم من جهة والمشرفين والزملاء من جهة أخرى، وتعزيز الثقة مع الادارة من خلال ايجاد منافذ للاحتكاك بينها وبين ورؤساء الاقسام ومساعديهم. Abstract: This study aimes to measur the degree of organizational trust of the heads of departments and their assistants at university of ghardaia, and this towards both of colleagues, supervisors and administration. We used in this study a questionnaire designed and distributed to the study community represented by the heads of departments and their assistants university colleges. The study found that there is a high degree of organizational trust of the heads of departments and their assistants at university of ghardaia toward their supervisors and their colleagues, while ther is no high degree of organizational trust toward administration. The study recommends maintaining the trust that exists between the heads of departments and their assistants on the one hand and supervisors and colleagues on the other hand, and strengthening trust with administration by finding opportunities for friction between them and the heads of departments and their assistants.
Keywords: ثقة تنظيمية ثقة بالمشرفين ثقة بالزملاء ثقة بالادارة